Omega-3 Fatty Acid Supplementation and Coronary Heart Disease Risks: A Meta-Analysis of Randomized Controlled Clinical Trials - Shen, ShiChun; Gong, Chen; Jin, KaiQin; Zhou, Lei; Xiao, Yin; Ma, Likun (Frontiers in Nutrition, 2022)
Abstract Background: The clinical benefits of omega-3 Fatty Acids (FA) supplementation in preventing and treating coronary heart disease (CHD) remain controversial. Therefore, this study aimed to investigate the clinical benefits of omega-3 FA supplementation, with special attention given to specific subgroups. Methods: Randomized controlled trials (RCTs) that compared the effects of omega-3 FA supplementation for CHD versus a control group and including at least 1,000 patients were eligible for inclusion in this meta-analysis. The relative risk (RR) of all-cause death, major adverse cardiovascular events (MACE), cardiovascular death, myocardial infarction (MI), stroke, and revascularization were estimated. We analyzed the association between cardiovascular risk and omega-3 FA supplementation in the total subjects. We focused on the cardiovascular risk compared to omega-3 FA in subgroups with different development stages of CHD, omega-3 FA supplementation application dose, diabetes, and sex. PROSPERO registration number: CRD42021282459. Results: This meta-analysis included 14 clinical RCTs, including 135,291 subjects. omega-3 FA supplementation reduced the risk of MACE (RR; 0.95; CI: 0.91-0.99; p for heterogeneity 0.27; I2=20%; P=0.03), cardiovascular death (RR; 0.94; CI: 0.89-0.99; p for heterogeneity 0.21; I2=25%; P=0.02), and MI (RR; 0.86; CI: 0.79-0.93; p for heterogeneity 0.28; I2=19%; P<0.01), but had no significant effect on all-cause death, stroke, and revascularization. In the subgroup analysis, omega-3 FA supplementation decreased the incidence of MACE and cardiovascular death in acute MI patients, the risk of MI and stroke in patients with CHD, and the risk of MI in patients with high-risk CHD. 0.8-1.2 g omega-3 FA supplementation reduced the risk of MACE, cardiovascular death, and MI. It was revealed that gender and diabetes have no significant association between omega-3 FA supplementation and MACE risk. Conclusions: omega-3 FA supplementation had a positive effect in reducing the incidence of MACE, cardiovascular death, MI. Regardless of the stage of CHD, omega-3 FA supplementation can prevent the occurrence of MI. The 0.8-1.2 g omega-3 FA supplementation alleviated CHD risk more effectively than lower or higher doses.